Nanostructured high-performance concretes based on low-strength aggregates - Rassokhin Aleksandr; Ponomarev Andrey; Karlina Antonina (Magazine of Civil Engineering, 2022)
In the modern world, construction is often located in remote and hard-to-reach regions, where there are no acceptable quality aggregates for concrete. The transportation of high-quality aggregates leads to a significant increase in the cost of concrete. This paper considers the possibility of developing high-performance concretes using aggregates available in the construction region. This is possible with the use of modern achievements in the field of construction science and construction chemistry, as well as nanotechnology. The strength and mineralogical properties of gneissic granite from the Kem river bed, as well as gabbro-diabase, were investigated. During the experimental work, a high-performance nanostructured concrete based on low-strength gneissic granite was developed. The strength and operational properties of the concrete were determined. The dynamic of gain in strength of concrete at the ages of 7, 28, and 180 days was also studied. The developed binder combination can also be used to produce high-performance concretes with other low-strength aggregates.